Analysis of the Mineral Content of Mountain Salt in South Krayan District: Implications for Local Food Health - Jemri, Jemri; Jannah, Harizatul; Hajar, Siti; Ramli, Ismail (Sean Institute, 2025)
This research focuses on analyzing the mineral content in mountain salt derived from saltwater sources in the mountainous area of Krayan, especially South Krayan. The main objective of this research is to identify the mineral content in mountain salt, with the hope that it can be further developed for economic, environmental, health, and scientific aspects. Potential uses include natural resource development, health and nutritional benefits, mountain salt-based industries, and sustainable mining practices. The research method involved laboratory testing using Atomic Absorption Spectrometer (SSA), X-Ray Difractometer (XRD), and Scanning Electron Microscopy (SEM). SSA results showed the content of minerals such as Na, K, Mg, Al, Cu, Zn, Fe, Ba, and Sr. XRD analysis identified the main peak of NaCl crystals with impurities of KCl, CaCl₂, MgCl₂, and AlCl₃. SEM observations revealed a cuboidal crystal morphology with a space group of Fm3m and a crystal lattice length of 5.620 Å. Overall, this study aims to understand the mineral composition of mountain salt and its implications for local food health.